1999
DOI: 10.1063/1.125194
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen diffusion into SiO2-capped GaN during annealing

Abstract: SiO 2 layers were deposited on p-GaN (hole concentration 9×1017 cm−3) by inductively coupled plasma chemical vapor deposition using an O17-enriched O2 precursor. The samples were then annealed at 500–900 °C and the SiO2 was removed. Secondary ion mass spectrometry profiling showed significant indiffusion of O17 into the GaN under these conditions, with an incorporation depth of ∼0.18 μm after the 900 °C anneal. The O17 diffusion profiles indicate that the high dislocation density in the GaN strongly affects th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
40
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(46 citation statements)
references
References 19 publications
6
40
0
Order By: Relevance
“…1, 2). Diffusion coefficient of oxygen calculated from the oxygen profile in epitaxial GaN amounts ~3×10 -13 cm 2 /s and is in good agreement with data reported in [7]. Diffusion rate was lower than MOCVD growth rate.…”
Section: Resultssupporting
confidence: 88%
“…1, 2). Diffusion coefficient of oxygen calculated from the oxygen profile in epitaxial GaN amounts ~3×10 -13 cm 2 /s and is in good agreement with data reported in [7]. Diffusion rate was lower than MOCVD growth rate.…”
Section: Resultssupporting
confidence: 88%
“…24 On the other hand, the diffusion of oxygen atoms by annealing at 500-900°C has been reported for SiO 2 / GaN interfaces. 25 Thus, it is highly likely that oxygen had a decaying distribution in the AlGaN layer before the surface control process and that this distribution was changed during the surface control process at 700°C. The result indicates that the present surface control process efficiently removes oxygen donors having a decaying distribution from the surface and realizes the intrinsic constant donor density of Si.…”
Section: C-v Characterization Of Surface Control Processmentioning
confidence: 99%
“…However, as there exist only a few experimental studies of oxygen in GaN, the fundamental origin and role of the oxygen in determining the overall electronic characteristics of the films is poorly understood. For example, it has been suggested that oxygen in GaN may originate as an impurity in the NH 3 precursor for metal organic chemical vapor deposition (MOCVD), or may originate from the remnant water vapor in molecular beam epitaxy (MBE) [5]. Another suggestion is that oxygen from the Al 2 O 3 substrate may diffuse within the disordered interfacial region, creating donors responsible for the formation of an impurity band [6].…”
mentioning
confidence: 99%